THE EFFECT OF REWARDS AND PUNISHMENT ON THE EMPLOYEE'S EMPLOYMENT AT PT. TANIA MEDAN SERVICE INSURANCE - Al Firah; Muhammad Ishak (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2023)
ABSTRACT The purpose of this research is to find out the impact of reward and punishment on the performance of employees on PT. Insurance Tania Medan. A reward that is not timely and not consistent with the employee's work. Evaluation of punishment for employees repeatedly committing the same mistake. Employee performance is less optimal due to the motivation of companies that are still less optimum. The population of 40 employees remains as a saturated sample. Data collection methods are observations, interviews, documentation, questionnaires. Data analysis techniques using double linear regression. The test results t obtained Sig reward and Sig punishment values of 0,000<0.05 then the variable is distributed normally. The test result F is 17.082 and the test value Sig is 0.000<0.05 then it is simultaneously variable so that Ha is accepted and means that the variables are simultaneusly influenced by the employee performance variable. The result of the test determination coefficient (R2) on the R Square column is 0.693, then the reward variable and punishement influence employee performances variables of 69.3% and the remaining 30.7% are affected by other variables other than these regression equations or variables not studied. Employee motivation and performance provided by the company will be very useful to boost employee confidence and drive employee performance by giving rewards when employees can their goals and punishment when employees are negligent in their work.Keywords: Reward, Punishment, Employee Performance